UPAYA MENINGKATKAN KOORDINASI DALAM MENGEMBANGKAN INDUSTRI PARIWISATA DI KABUPATEN WONOSOBO - Sukron Amin; Fathurrohman Fathurrohman; Zaenal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Coordination is absolutely essential in a good organization of public organizations as well as private organizations. Coordination is carried out to create a uniform and harmonious effort on target. In an effort to develop the region's tourism industry, cross-sector coordination is needed to help harmonize and synchronize the roles of the actors of development, namely the Government, the private and the public. Coordination is needed from the level of planning up to evaluation activities.Research used are a descriptive qualitative, and thus use the phenomenon in which it contained the principal interview. Phenomenon that be used as reference is the delegation of authority, communication, budget, the coordinator, the mechanism of a pattern of coordination. The phenomenon that is then be used as reference to know the role of coordination and thruster and inhibitors factor in improving the coordination of traffic sectors. An interview conducted to 3 head of dept. namely dept. of tourism and culture communication and informatic department of transportation, district wonosobo, public works department and one of the owner of the bureau of tourism.Based on the results of the interview has been done can be noted that in the development of the tourism industry, involving the role of the Government (Office of tourism and culture, public works, Transportation and Communication Department of Informatics) private (travel agency tourism) and the role of the community. Therefore cross-cutting coordination is needed both in the planning, implementation and evaluation process of course with effective communication. The active role of the actors of development becomes the driving factor in coordination, and differences in the orientation of the time and also the limited budget of dijadiakan inhibitor of factor, because each implementation activity, each of these actors do not have the same time and an adequate budget.